Keefektifan Model Pembelajaran CIRC terhadap Kemampuan Membaca Pemahaman Teks Eksposisi Peserta Didik Kelas V SD Islam Imama - Nurunnada, Haniyya; Nuryanto, Sukarir (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Students' low reading comprehension skills make them unable to understand a reading that becomes a bridge of various knowledge. Then, a learning model is needed to help students improve reading comprehension skills. This study was conducted with the aim of knowing the effectiveness of the CIRC learning model in 5th-grade students of Imama Islamic Elementary School. This type of research is experimental with a quasi-experimental design in the form of a non-equivalent control group design. This study's experimental and control classes were in grades 5C and 5A. Hypothesis data analysis using paired sample t-test, independent sample t-test, and N-Gain score. Based on the results of the paired sample t-test hypothesis test, a significance value of 0.001<0.05 was obtained, which means that there is a significant difference between the learning outcomes of the experimental and control classes. Furthermore, in the independent sample t-test hypothesis test, the Sig. value is obtained. (two-sided p) of 0.006<0.05, there is an average difference in reading comprehension ability. Based on the N-Gain score results, it was found that the average N-Gain value was 46.8%. This result is interpreted to be included in the less effective category. It can be concluded that the CIRC learning model can significantly improve students' ability to read comprehension of expository text. Still, it is less effective in enhancing students' ability to read comprehension in grade 5 of Imama Islamic Elementary School.